If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1.83) = 4x Reorder the terms: 5(1.83 + x) = 4x (1.83 * 5 + x * 5) = 4x (9.15 + 5x) = 4x Solving 9.15 + 5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9.15 + 5x + -4x = 4x + -4x Combine like terms: 5x + -4x = 1x 9.15 + 1x = 4x + -4x Combine like terms: 4x + -4x = 0 9.15 + 1x = 0 Add '-9.15' to each side of the equation. 9.15 + -9.15 + 1x = 0 + -9.15 Combine like terms: 9.15 + -9.15 = 0.00 0.00 + 1x = 0 + -9.15 1x = 0 + -9.15 Combine like terms: 0 + -9.15 = -9.15 1x = -9.15 Divide each side by '1'. x = -9.15 Simplifying x = -9.15
| 3/5x-2/3=4/5 | | -3f+5=14 | | 4(7-2x)-10=6x | | 0.4x+0.1=-1.1 | | x/8=45/10 | | 7(x-6.2)=2.1 | | 4x-2.5+3.8=61 | | 12/.75 | | (x^2)+4+x+30+90=180 | | 11+m=4m-1 | | 8x+8.18=2x+17 | | 2(x+1)+6=10-3x | | (3x-12)+(5x-34)=90 | | (3cosx)*(2cosx)= | | 3x/6=7x-6x/2 | | -4.6x+2.3=-20.7 | | Sin64=16/x | | x+3x-12+5x-34=180 | | -4x-45=39 | | 6x+4y=3.5 | | 3(x+4)-2(2+2x)=3(x-6+12+2) | | 9-2(x+4)=8(3-x)+1 | | -14.3=-1.8-3D | | 5-22=5x-4-4x | | 9×1/1000 | | 14x+9y=18p | | -150=-6(1-6x) | | 15u=135 | | x-2x=5+x | | 20th-8x=x-8 | | y=cos3/4x | | .2x+x^2=0 |